Analisis Butir Soal Ujian Akhir Semester Ganjil Madrasah Aliyah Walisongo Tapung Kampar - Rahmat Basuki; Asmal May; Hikmah (INTIFA: Journal of Education and Language, 2024)
The focus of this research is to analyze the odd semester final exam questions in the Arabic language subject for class X-IPS students at MA Walisongo Tapung Kampar for the 2022/2023 academic year. The goal is for Arabic language teachers to be able to create good measuring tools to measure students' level of understanding. The research uses a quantitative approach with a data collection model obtained from student answer sheet documents. The data obtained were analyzed using the Ms program. Excel and explained descriptively based on the level of validity, reliability and difficulty of each multiple choice question item. The research results show: (1) The results of the validity test found that from question numbers 1-15, 9 questions were included in the valid question category (60%) and 6 questions were included in the invalid question category (40%). (2) The results of the reliability test using the RK20 formula showed that the level of reliability of the multiple choice question test was 0.6, this shows that it is included in the medium category. (3) The results of the analysis of the level of difficulty show that between questions 1 to 15 there are 10 questions (33.33%) which are included in the "Easy" question category, 1 question item (6.67%) is included in the "Medium" question category. and 4 questions (26.67%) were included in the "Difficult" question category.